GONAD MATURITY STAGES OF ANCHOVIES (Encrasicholina heterolobus) FROM BACAN ISLAND - Retno Andarmari; Margaret Farmer; Umi Khodriyah; Andriko N. Susanto (Indonesian Fisheries Research Journal, 1998)
The gonad maturity stages of anchovies (Enrasirholina hetentlobus) used as tuna baitfish were examined in the waters of Bacan Island. The species is a multiple spawner with asynchrounous oocyte development.